Prevalence of large‐for‐gestational age and macrosomia among livebirths in 23 low‐ and middle‐income countries between 2000 and 2021: An individual participant data analysis - Kirakoya‐Samadoulougou, Fati; Ukwishaka, Joyeuse; Ngwasiri, Calypse; Subedi, Seema; Hazel, Elizabeth A.; Erchick, Daniel J.; Wu, Lee Shu Fune; Grandi, Carlos; Lachat, Carl; Toe, Laéticia Céline; Roberfroid, Dominique; Huybregts, Lieven; et al. (Wiley, 2025)
Objective To examine the prevalence of large‐for‐gestational age (LGA) and macrosomia in 23 countries between 2000 and 2021.